Doping of superalkali and superhalogen on graphene quantum dot surfaces to enhance nonlinear optical response: An efficient strategy for fabricating novel electro-optical materials. (October 2022) - Umar, Ali; Yaqoob, Junaid; Khan, Muhammad Usman; Hussain, Riaz; Alhadhrami, A.; Almalki, Abdulraheem S.A.; Janjua, Muhammad Ramzan Saeed Ashraf
Abstract: Graphene quantum dots are evolving as a popular novel class of organic nonlinear optical (NLO) materials, with applications in optoelectronics, nanocomposites, and many other areas. Tetragonal graphene quantum dots (T-GQDs) doped with superalkalis (Li3 O, Li4 N) and superhalogens (BeF3, BF4 ) have been investigated here with regard to their geometrical, thermodynamic, electronic, and NLO properties by means of density functional theory (DFT) calculations at the B3LYP level. Computational studies reflect the high stability of these complexes, and indicate interaction with the dopants at the top of a cavity. Interaction energies of dopant molecules suggest the feasibility of their complexation on a T-GQD sheet, with an isomer of BF4 @T-GQD showing the highest interaction energy (Eint ) of −97.15 kcal mol −1 . HOMO-LUMO energy gaps (EH-L ) yield the lowest band gap (0.23 eV) for an isomer of Li3 O@T-GQD, which in turn enhances the NLO response. A significant increase in NLO response is noted for all of the reported complexes, particularly for superalkali-doped Li4 N@T-GQD, which displays a first hyperpolarizability ( β o ) of 4.5 × 10 4 a.u. Moreover, absorption phenomena prove that the resultant complexes retain viable deep-ultraviolet (UV) transparency. Natural bond order (NBO) and density of states (DOS) analyses further verify charge transfer and the establishment of new states in the complexes. All of the results manifest the distinction of superalkali- and superhalogen-doping on T-GQD, with superalkali being an electron-donating entity and superhalogen showing electron-withdrawing behavior. We conclude that superalkali-doped Li4 N@T-GQD and superhalogen-doped BF4 @T-GQD complexes (isomers f and l ) may serve as excellent alternatives to current NLO materials. Hence, this study may pave the way for the fabrication of thermally stable graphene quantum dot complexes as valuable precursors for highly efficient NLO materials. Graphical abstract: Image 1 Highlights: Graphene quantum dot complexes have been studied for highly efficient NLO materials. Doping of superalkali and superhalogen on graphene quantum dot has been performed. An efficient strategy to fabricate novel electro-optical materials has been proposed.